2009
DOI: 10.1111/j.1365-294x.2009.04384.x
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian chytridiomycosis in Japan: distribution, haplotypes and possible route of entry into Japan

Abstract: A serious disease of amphibians caused by the chytrid fungus Batrachochytrium dendrobatidis was first found in Japan in December 2006 in imported pet frogs. This was the first report of chytridiomycosis in Asia. To assess the risk of pandemic chytridiomycosis to Japanese frogs, we surveyed the distribution of the fungus among captive and wild frog populations. We established a nested PCR assay that uses two pairs of PCR primers to amplify the internal transcribed spacer (ITS) region of a ribosomal RNA cassette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
303
2
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(331 citation statements)
references
References 51 publications
(61 reference statements)
18
303
2
8
Order By: Relevance
“…Research has recently suggested the existence of a Bd lineage that is associated with the Japanese giant salamander, Andrias japonicus (22). This lineage, defined by sequencing a short fragment of the ribosomal DNA, is dissimilar to the rDNA sequences of BdGPL, which nonnative North American bullfrogs have introduced to Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Research has recently suggested the existence of a Bd lineage that is associated with the Japanese giant salamander, Andrias japonicus (22). This lineage, defined by sequencing a short fragment of the ribosomal DNA, is dissimilar to the rDNA sequences of BdGPL, which nonnative North American bullfrogs have introduced to Japan.…”
Section: Discussionmentioning
confidence: 99%
“…sudden appearance, strong virulence, and rapid transmission) [5]. Investigations of museum specimens collected from as far back as 1902 in Japan [6] and 1938 in Africa [7] have detected Bd in skin cross sections. On the other hand, long-term population studies since the 1900's had no records of mass mortalities until the late 1970's when the first Bd epidemics were reported [8].…”
Section: Introductionmentioning
confidence: 99%
“…Is Bd a newly emerged pathogen recently introduced to areas by animal (including human) or other vectors where it is causing population declines (Novel Pathogen Hypothesis), or is Bd an endemic parasite and recent disease emergences are attributable to increased virulence caused by (human-mediated) ecological and environmental changes (Endemic Pathogen Hypothesis; Rachowicz et al 2005;Skerrat et al 2007)? Some authors argue that both mechanisms contribute to the existing distribution of presence, prevalence and disease (Goka et al 2009;Walker et al 2010) but the fundamental question regarding introduction remains valid, as efforts to mitigate disease may differ based on whether a pathogen is introduced or not. Evidence in support of introduction includes the presence of infection in commercially traded amphibian species both at source and in invasive populations (Mazzoni et al 2003;Weldon et al 2004;Fisher & Garner 2007).…”
Section: What Can Be Said About the Origin Of Bd In Italy?mentioning
confidence: 99%